STRUCTURE AND MORPHOMETRICS OF THE OLFACTORY ORGANS OF A FRESHWATER MAJOR CARP, CATLA CATLA (HAM.) - PANDEY, ANITA; KUNWAR, GOPAL KRISHNA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1990)
The structure and morphometrics of the olfactory organs of a freshwater major carp, C. Catla have been described and the data have been analysed with respect to body weight using logarithmic transformations (log Y = log a + b. log W). The slope of the regression line for total olfactory surface area is 0.6826.